(untitled) (EAAE Joint Publishings, 2026)
This paper asks what can we learn from homeowner modifications of manufactured homes about addressing resilience, accommodation, energy savings, occupation, and flexibility? The authors identify retrofits which decrease heating and/or cooling requirements; provide long term accessibility as owner’s age; plan resilience in the face of extreme weather; and enhance quality of life aligned with local culture. Three rural extreme climates in Louisiana, Arizona, and Colorado provide data on a wide range of solutions tailored to the particularities of climate conditions. The resulting assessment identifies categories of modifications and retrofits and associated typologies, for example homes on piers, unconditioned porch or carport additions, conditioned additions, envelope modifications, and changes to provide ADA accessibility. Quantified assessment through energy and structural modeling evaluates the effectiveness of the homeowner designed retrofits observed in Louisiana, Arizona, and Colorado. The results of assessment reveal that homeowners decreased EUI through simple passive methods adapted from agricultural, aquacultural, and industrial architecture. Energy modeling simulation on case studies for observed retrofit roof assemblies showed up to a 28% decrease in EUI in Louisiana, and 58% decrease in EUI in Arizona. These same retrofits produce large exterior covered occupiable spaces which provide an extended period of thermal comfort by over 20%. While the paper primarily focuses upon assessment of heating/cooling mitigation through roof assembly retrofit, it also discusses: structural changes through the addition of piers, super structure, and lifting systems along with accessibility and circulation changes, all due to accommodation of FEMA base flood height elevation in Louisiana; window retrofits, window shading, and understory/crawlspace protection and skirting to both provide resilience during climatic events, but also to mitigate heat transfer in manufactured homes in Arizona and Colorado; and heating/cooling source retrofits and augmentation in all three locations.